2015
DOI: 10.1016/j.rehab.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory neuromodulation in patients with neurological pathologies: For whom and how?

Abstract: Implanted phrenic nerve stimulation is a technique restoring spontaneous breathing in patients with respiratory control failure, leading to being dependent on mechanical ventilation. This is the case for quadriplegic patients with a high spinal cord injury level and for patients with congenital central hypoventilation syndrome. The electrophysiological diaphragm explorations permits better patient selection, confirming on the one hand a definite issue with central respiratory command and on the other hand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…The management of post-SCI respiratory dysfunction using open-loop muscle/nerve FES (e.g. diaphragm pacing (Gonzalez-Bermejo et al, 2015; Onders, 2012; Onders et al, 2014; Posluszny et al, 2014)), represents a significant improvement over alternative assisted-ventilation strategies. Ongoing work in this area has revealed that it not only maintains ventilation, but may also contribute to plasticity and lasting functional recovery (Posluszny et al, 2014).…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…The management of post-SCI respiratory dysfunction using open-loop muscle/nerve FES (e.g. diaphragm pacing (Gonzalez-Bermejo et al, 2015; Onders, 2012; Onders et al, 2014; Posluszny et al, 2014)), represents a significant improvement over alternative assisted-ventilation strategies. Ongoing work in this area has revealed that it not only maintains ventilation, but may also contribute to plasticity and lasting functional recovery (Posluszny et al, 2014).…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
“…Unfortunately, not all injured individuals are eligible for phrenic nerve stimulation or diaphragm pacing as intact phrenic motoneurons (distributed C3-C5) and phrenic nerves are required in order to elicit muscle contraction (DiMarco et al, 2005a; Gonzalez-Bermejo et al, 2015). Injuries directly compromising the C3-5 spinal cord or resulting in root avulsion/nerve damage typically result in a paralyzed diaphragm that cannot be stimulated.…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
“…Lower cervical lesions at the C4/C5 spinal levels usually result in partial reduction of diaphragm activity. Mechanical ventilation (MV) via a tracheostomy is standard therapy for patients with tetraplegia after complete cervical SCI at or above the C3, and it is common among those with complete cervical injuries distal to C3 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The chronic use of MV is associated with significant complications that effect quality of life including difficulty in speech, loss of smell, increased secretions requiring regular suctioning, and noise associated with the ventilator. Ventilated patients also experience high rates of complications, including posterior lobe atelectasis, pneumonia, barotrauma, tracheomalacia, and a significant reduction in life expectancy [3]. To address these negative effects of MV, technologies to stimulate the diaphragm through direct electrical stimulation of the PN motor points or indirectly through stimulation of the PNs have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…So results of sporadic patients treated with immunosuppressive agents, antiviral agents or intravenous immunoglobulins must be interpreted with caution [ 10 ]. Phrenic nerve pacing is no option as it requires intact phrenic nerve function [ 11 ].…”
Section: Discussionmentioning
confidence: 99%